?PREPARATION, CHARACTERIZATION AND MOLECULAR MODELS OF THE COMPLEXES OF QUADRIDENTATE TRIPODAL LIGAND TREN [TREN = TRIS(2-AMINOETHYL)AMINE] WITH Ag(I), Cd(II), Hg(II), Zr(IV) AND U(VI) (Biological Sciences - PJSIR, 2003)
The tripodal ligand tren, has been reacted with Ag(I), Cd(II), Hg(II), Zr(IV) and U(VI) in the EtOH medium. The solid product obtained immediately after the reaction, were formulated by comparing C, H, N, and S analysis data. Ag(I) and Cd(II) form simple five coordinated compounds and the others produce double salt like compounds. The bonding patterns of the compounds have been discussed on the basis of IR an UV visible spectral analysis. The geometry of the coordination sphere of the complexes are suggested on the basis of molecular models.